Monetary policy and economic growth in Ghana: Does financial development matter? - Prince Mike Sena; Grace Nkansa Asante; William Gabriel Brafu-Insaidoo (Cogent Economics & Finance, 2021)
The link between financial development and monetary policy has received considerable attention in many African countries but empirical evidence on the link has been mixed. By the use of the Autoregressive Distributed Lag (ARDL) approach, this study investigated whether financial development influences the effectiveness of monetary policy and assessed their joint effect on economic growth in Ghana for the period 1980 to 2016. The results revealed that financial development strengthens the effectiveness of monetary policy on economic growth in Ghana. The study therefore recommended that Bank of Ghana should further deepen financial sector development and improve on the competitiveness of financial markets in order to improve on the capacity of monetary policy in enhancing growth of the economy.
Keywords: 330; Autoregressive distributed lags; economic growth; financial development; Ghana; monetary policy; output